Incidence and structure of sudden cardiac death among working population of the Bryansk region. GERMINA register data - R. M. Linchak; A. M. Nedbaykin; E. V. Sementsova; I. A. Yusova; V. V. Strukova (Рациональная фармакотерапия в кардиологии)
Aim. To study the incidence and structure of sudden cardiac death (SCD) among the working population of the Bryansk region, as well as to determine its share in the structure of total and cardiovascular mortality in this age group.Material and methods. We analyzed the structure and incidence of SCD in 417740 people of working age (25-64 years) in five major areas of the Bryansk region and the city of Bryansk in 2012. Medical records (outpatient card, patient’s chart, autopsy protocol, a medical certificate of death) of 1447 people of working age who died from diseases of the circulatory system were analyzed.Results. 106 cases corresponded to the criteria for SCD, which determined the frequency of SCD 25.4 per 100000 working-age population. The predominance of men over women (85% vs 15%) was marked. Only 24% of cases of SCD occurred in hospitals, while 76% - in outpatient settings. A strong association between SCD and age was noted. Chronic (43%) and acute (37%) forms of ischemic heart disease turned out to be the main clinical entities that caused SCD.Conclusion. The share of SCD in total and cardiovascular mortality was 2.9% and 7.3% respectively. Strong correlation between SCD rate and age was found. Chronic and acute forms of ischemic heart disease turned out to be the main clinical entities that caused SCD.